Enhancing teaching and learning of fluid mechanics with interactive computational modelling - Neves, Rui (2017)
Talk given by Rui Neves at the GIREP-ICPE-EPEC 2017 Conference held from 3rd-7th July 2017 at Dublin City University, Dublin, Ireland.